A biodegradable plastic bag and preparation method thereof
By combining polylactic acid, PBAT, modified gluten, silane coupling agent modified chitosan and other ingredients, and through enzymatic reaction and heat treatment, biodegradable plastic bags with excellent mechanical properties were prepared, which solved the problem of poor mechanical properties of existing plastic bags, achieved stronger tensile strength and elongation of break, while maintaining biodegradable properties.
Patent Information
- Application Number
- CN202411160738.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The existing biodegradable plastic bags have poor mechanical properties, resulting in prone to rupture and water seepage of the solution.
Using a combination of polylactic acid, PBAT, modified gluten, silane coupling agent modified chitosan, lubricant and antioxidant, biodegradable plastic bags with excellent mechanical properties are prepared through enzymatic reaction and heat treatment steps.
It significantly improves the mechanical properties of biodegradable plastic bags, enhances its tensile strength and elongation at break, while maintaining its biodegradable properties.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic preparation, and in particular relates to a biodegradable plastic bag and a preparation method thereof. Background Art
[0002] As we all know, plastic products have the advantages of being cheap, light, durable, and plastic, and are therefore used in industries such as construction, transportation, packaging, and agricultural production. Disposable plastic bags are the most widely used. As people pay more attention to environmental issues, the treatment of discarded plastic bags has gradually attracted people's attention. The conventional treatment method for discarded plastic bags is landfill, but there is a problem of long-term non-degradability. Based on this, biodegradable plastic bags have attracted much attention due to their advantages such as biodegradability, non-toxicity, and high recyclability.
[0003] Biodegradable plastics refer to plastics that can be decomposed into small molecule inorganic substances such as CO2, H2O, and methane by microorganisms such as bacteria, fungi, and algae existing in nature under the action of enzymes. There are many types of biodegradable plastic bags on the market, but most of them have technical problems such as poor mechanical properties. For example, Chinese patent CN201810626539.6 discloses an easily degradable and environmentally friendly plastic bag, which uses plant starch as a raw material for preparation. However, the high content of plant starch reduces the mechanical properties of the plastic bag, causing the plastic bag to break easily and the solution to seep water. In view of this, there is an urgent need for a deeper exploration and research and development of the mechanical properties of plastic bags. Summary of the invention
[0004] The first object of the present invention is to provide a biodegradable plastic bag having excellent mechanical properties.
[0005] The second object of the present invention is to provide a method for preparing a biodegradable plastic bag. The preparation method has simple steps and is easy to put into actual production.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A biodegradable plastic bag comprises the following ingredients: 60-80 parts of polylactic acid, 30-40 parts of PBAT, 10-17 parts of modified gluten powder, 5-10 parts of chitosan modified by a silane coupling agent, 0.5-1 parts of a lubricant, and 0.1-0.5 parts of an antioxidant;
[0008] The preparation process of the modified gluten is as follows:
[0009] (1) adding gluten powder to water and uniformly dispersing it by ultrasonication to obtain solution A;
[0010] (2) adding ε-polylysine and cucurbituril to water and uniformly dispersing them by ultrasonication to obtain solution B;
[0011] (3) The solution A and the solution B are mixed, glutaminase is added to perform enzymatic hydrolysis, and the reaction solution is freeze-dried to obtain modified gluten powder.
[0012] Furthermore, in step (1), the mass ratio of gluten to water is 1:1-2.
[0013] Furthermore, in step (2), the mass ratio of ε-polylysine to cucurbituril and water is 1:3-5:20-30, and the cucurbituril is cucurbituril [6].
[0014] Furthermore, in step (3), the temperature of the enzymatic hydrolysis reaction is 40-45° C., the pH is 6-7, the time is 4-8 h, the enzyme activity of the glutaminase is 1000 U / g, and the amount of glutaminase used is 0.5-1% of the mass of the gluten powder.
[0015] Furthermore, the preparation process of the silane coupling agent modified chitosan is as follows: chitosan and silane coupling agent are mixed according to a mass ratio of 1:0.3-0.5, heated to 80-90° C. and reacted for 2-3 hours to obtain silane coupling agent modified chitosan.
[0016] Furthermore, the silane coupling agent is selected from one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
[0017] Furthermore, the antioxidant is antioxidant 1010 or antioxidant 1076.
[0018] Furthermore, the lubricant is stearyl stearate or paraffin.
[0019] The preparation method of the biodegradable plastic bag comprises the following steps: vacuum drying the components and heating them to 180-200°C for 1-2 hours to obtain a mixture, and extruding the mixture and cooling it to form the mixture.
[0020] Furthermore, the vacuum drying is carried out at a temperature of 90-100° C. and a time of 0.8-1 h.
[0021] The beneficial technical effects of the present invention are:
[0022] (1) Improve the performance of gluten
[0023] The mixed solution of ε-polylysine, cucurbituril and gluten was enzymatically hydrolyzed by glutaminase to obtain modified gluten which can enhance the mechanical properties of biodegradable plastic bags.
[0024] (2) The preparation method is simple and concise
[0025] The present invention also provides a method for preparing a biodegradable plastic bag, which has simple steps and is easy to operate and practice. The biodegradable plastic bag prepared by the method has both excellent mechanical properties and biodegradability. DETAILED DESCRIPTION
[0026] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0027] (I) Preparation Example
[0028] Preparation Example 1
[0029] A modified gluten powder, the specific preparation process of the modified gluten powder is as follows:
[0030] (1) adding gluten to water at a mass ratio of gluten to water of 1:1.5, and uniformly dispersing by ultrasonication to obtain a solution A;
[0031] (2) adding ε-polylysine and cucurbituril [6] to water in a mass ratio of ε-polylysine, cucurbituril [6], and water of 1:4:25, and uniformly dispersing by ultrasonication to obtain a solution B;
[0032] (3) Solution A obtained in step (1) and solution B obtained in step (2) are mixed, and glutaminase with an enzyme activity of 1000 U / g is added, and the amount of glutaminase added is 0.8% of the mass of gluten powder. The enzymatic hydrolysis reaction is carried out at 42° C. and pH 6.4 for 6 h. After the reaction is completed, the reaction solution is freeze-dried to obtain modified gluten powder.
[0033] Preparation Example 2
[0034] A modified gluten powder, the specific preparation process of the modified gluten powder is as follows:
[0035] (1) adding gluten to water in a mass ratio of gluten to water of 1:1, and uniformly dispersing the gluten by ultrasonication to obtain a solution A;
[0036] (2) adding ε-polylysine and cucurbituril [6] to water in a mass ratio of ε-polylysine, cucurbituril [6], and water of 1:3:20, and uniformly dispersing by ultrasonication to obtain a solution B;
[0037] (3) Solution A obtained in step (1) and solution B obtained in step (2) are mixed, and glutaminase with an enzyme activity of 1000 U / g is added, and the amount of glutaminase added is 1% of the mass of gluten powder. The enzymatic hydrolysis reaction is carried out at 40° C. and pH 6 for 4 hours. After the reaction is completed, the reaction solution is freeze-dried to obtain modified gluten powder.
[0038] Preparation Example 3
[0039] A modified gluten powder, the specific preparation process of the modified gluten powder is as follows:
[0040] (1) adding gluten to water in a mass ratio of gluten to water of 1:2, and uniformly dispersing the gluten by ultrasonication to obtain a solution A;
[0041] (2) adding ε-polylysine and cucurbituril [6] to water in a mass ratio of ε-polylysine, cucurbituril [6], and water of 1:5:30, and uniformly dispersing by ultrasonication to obtain a solution B;
[0042] (3) Solution A obtained in step (1) and solution B obtained in step (2) are mixed, and glutaminase with an enzyme activity of 1000 U / g is added, and the amount of glutaminase added is 0.5% of the mass of gluten powder. The enzymatic hydrolysis reaction is carried out at 45° C. and pH 7 for 8 h. After the reaction is completed, the reaction solution is freeze-dried to obtain modified gluten powder.
[0043] Preparation Example 4
[0044] A silane coupling agent modified chitosan, the specific preparation process of the silane coupling agent modified chitosan is as follows:
[0045] Chitosan and silane coupling agent KH-550 were mixed in a mass ratio of 1:0.4, and then heated to 85° C. for reaction for 2.5 h to obtain silane coupling agent modified chitosan.
[0046] Preparation Example 5
[0047] A silane coupling agent modified chitosan, the specific preparation process of the silane coupling agent modified chitosan is as follows:
[0048] Chitosan and silane coupling agent KH-560 were mixed in a mass ratio of 1:0.3, and then heated to 90° C. for reaction for 2 h to obtain silane coupling agent modified chitosan.
[0049] Preparation Example 6
[0050] A silane coupling agent modified chitosan, the specific preparation process of the silane coupling agent modified chitosan is as follows:
[0051] Chitosan and silane coupling agent KH-570 were mixed in a mass ratio of 1:0.5, and then heated to 80° C. for reaction for 3 h to obtain silane coupling agent modified chitosan.
[0052] (II) Embodiment
[0053] Example 1
[0054] A biodegradable plastic bag is composed of the following components: 64 parts of polylactic acid, 31 parts of PBAT, 12 parts of modified gluten powder prepared in Preparation Example 1, 8 parts of silane coupling agent modified chitosan prepared in Preparation Example 4, 0.9 parts of paraffin wax, and 0.4 parts of antioxidant 1076.
[0055] This embodiment also provides a method for preparing a biodegradable plastic bag, and the specific preparation process is as follows:
[0056] The ingredients in the above formula were placed in a vacuum drying oven, dried at 95°C for 0.9h, then heated to 190°C and kept warm for 1.5h to obtain a mixture, which was extruded through an extruder and formed after being cooled to room temperature.
[0057] Example 2
[0058] A biodegradable plastic bag is composed of the following components: 64 parts of polylactic acid, 31 parts of PBAT, 12 parts of modified gluten powder prepared in Preparation Example 2, 8 parts of silane coupling agent modified chitosan prepared in Preparation Example 5, 0.9 parts of paraffin wax, and 0.4 parts of antioxidant 1010.
[0059] This embodiment also provides a method for preparing a biodegradable plastic bag, and the specific preparation process is as follows:
[0060] The ingredients in the above formula are placed in a vacuum drying oven, dried at 90°C for 1 hour, then heated to 180°C and kept warm for 2 hours to obtain a mixture, which is extruded through an extruder and formed after being cooled to room temperature.
[0061] Example 3
[0062] A biodegradable plastic bag is composed of the following components: 64 parts of polylactic acid, 31 parts of PBAT, 12 parts of modified gluten powder prepared in Preparation Example 3, 8 parts of silane coupling agent modified chitosan prepared in Preparation Example 6, 0.9 parts of octadecyl stearate, and 0.4 parts of antioxidant 1076.
[0063] This embodiment also provides a method for preparing a biodegradable plastic bag, and the specific preparation process is as follows:
[0064] The ingredients in the above formula are placed in a vacuum drying oven, dried at 100°C for 0.8h, then heated to 200°C and kept warm for 1h to obtain a mixture, which is extruded through an extruder and molded after being cooled to room temperature.
[0065] (III) Comparative ratio
[0066] Comparative Example 1
[0067] A plastic bag is composed of the following ingredients: 64 parts of polylactic acid, 31 parts of PBAT, 12 parts of gluten, 8 parts of chitosan modified by silane coupling agent obtained in Preparation Example 4, 0.9 parts of paraffin, and 0.4 parts of antioxidant 1076. The rest is the same as in Example 1.
[0068] Comparative Example 2
[0069] A plastic bag, the plastic bag is composed of the following ingredients: 64 parts of polylactic acid, 31 parts of PBAT, 2 parts of gluten, 2 parts of ε-polylysine, 8 parts of cucurbituril [6], 8 parts of silane coupling agent modified chitosan prepared in Preparation Example 4, 0.9 parts of paraffin wax, 0.4 parts of antioxidant 1076, and the rest is the same as in Example 1.
[0070] Comparative Example 3
[0071] A plastic bag is composed of the following ingredients: 64 parts of polylactic acid, 31 parts of PBAT, 8 parts of chitosan modified by silane coupling agent obtained in Preparation Example 4, 0.9 parts of paraffin wax, and 0.4 parts of antioxidant 1076. The rest is the same as in Example 1.
[0072] Comparative Example 4
[0073] A plastic bag is composed of the following ingredients: 64 parts of polylactic acid, 31 parts of PBAT, 12 parts of modified gluten powder obtained in Preparation Example 1, 2.3 parts of silane coupling agent KH-550, 5.7 parts of chitosan, 0.9 parts of paraffin, 0.4 parts of antioxidant 1076, and the rest are the same as in Example 1.
[0074] (IV) Experimental Examples
[0075] Experimental Example 1
[0076] This experimental example explores the biodegradability of the plastic bags of Examples 1-3 and Comparative Examples 1-4. The specific detection method is as follows:
[0077] According to GB / T20197-2006, the biodegradability of the plastic bags of Examples 1-3 and Comparative Examples 1-4 after 60 days and 120 days of landfill was tested. Each group was tested 5 times and the average value was taken. The test results are shown in Table 1-2.
[0078] Table 1 Biodegradation performance of plastic bags of Examples 1-3 and Comparative Examples 1-4 after 60 days of landfill
[0079] Grouping first Second time The third time Fourth Fifth average value Example 1 73.19 73.87 69.96 72.03 71.08 72.03 Example 2 69.66 72.78 73.21 70.02 72.30 71.59 Example 3 69.92 71.46 72.20 69.58 72.76 71.18 Comparative Example 1 71.72 68.01 71.53 71.66 71.90 70.96 Comparative Example 2 71.56 71.98 70.15 69.33 73.25 71.25 Comparative Example 3 71.86 69.04 69.66 72.48 71.29 70.87 Comparative Example 4 68.84 69.82 72.29 68.97 71.76 70.34
[0080] Table 2 Biodegradation performance of plastic bags of Examples 1-3 and Comparative Examples 1-4 after 120 days of landfill
[0081] Grouping first Second time The third time Fourth Fifth average value Example 1 99.75 99.66 99.51 99.62 99.54 99.62 Example 2 99.73 99.54 99.54 99.69 99.72 99.64 Example 3 99.55 99.53 99.57 99.60 99.58 99.57 Comparative Example 1 99.51 99.49 99.50 99.48 99.50 99.50 Comparative Example 2 99.61 99.59 99.63 99.59 99.61 99.61 Comparative Example 3 99.56 99.53 99.49 99.56 99.54 99.54 Comparative Example 4 99.64 99.49 99.59 99.57 99.59 99.58
[0082] It can be seen from Table 1-2 that the plastic bags of Examples 1-3 and Comparative Examples 1-4 have excellent biodegradability.
[0083] Experimental Example 2
[0084] This experimental example explores the mechanical properties of the plastic bags of Examples 1-3 and Comparative Examples 1-4. The specific testing methods are as follows:
[0085] ① Tensile properties: The tensile test was carried out on a universal material testing machine according to the plastic tensile properties test standard GB / T 1040.3-2006. The tensile rate was 2 mm / min. Each group was tested 5 times and the average value was taken. The results are shown in Table 3.
[0086] ② Elongation at break: According to the plastic tensile properties test standard GB / T 1040.3-2006, a tensile test was carried out on a universal material testing machine. The tensile rate was 2 mm / min. Each group was tested 5 times and the average value was taken. The results are shown in Table 4.
[0087] Table 3 Tensile strength of plastic bags of Examples 1-3 and Comparative Examples 1-4
[0088] Grouping / tensile strength (MPa) first Second time The third time Fourth Fifth average value Example 1 57.42 58.32 59.94 60.29 59.80 59.15 Example 2 59.38 60.57 59.83 57.20 57.19 58.83 Example 3 56.67 60.22 59.61 58.29 56.64 58.29 Comparative Example 1 51.16 52.09 49.31 50.32 50.3 50.64 Comparative Example 2 50.06 50.9 52.64 52.79 50.84 51.45 Comparative Example 3 46.17 44.59 44.38 44.02 42.72 44.38 Comparative Example 4 50.49 52.64 52.99 53.07 51.18 52.07
[0089] Table 4 Elongation at break of plastic bags of Examples 1-3 and Comparative Examples 1-4
[0090] Grouping / elongation at break (%) first Second time The third time Fourth Fifth average value Example 1 466 466 464 464 458 464 Example 2 460 459 456 460 459 459 Example 3 453 452 451 454 457 453 Comparative Example 1 375 376 378 377 382 378 Comparative Example 2 389 390 392 391 395 391 Comparative Example 3 290 286 302 292 288 292 Comparative Example 4 399 408 402 410 409 406
[0091] It can be seen from Tables 3-4 that the mechanical properties of the plastic bags of Comparative Examples 1-3 are reduced compared with Examples 1-3. Further analysis shows that the mechanical properties of the plastic bags prepared in Comparative Example 1 using gluten instead of modified gluten, the plastic bags prepared in Comparative Example 2 using gluten, ε-polylysine and cucurbituril instead of modified gluten, and the plastic bags prepared in Comparative Example 3 without using modified gluten are all reduced. It can be seen from the above that the modified gluten prepared by the present invention can enhance the mechanical properties of plastic bags.
[0092] Compared with Examples 1-3, the mechanical properties of the plastic bag in Comparative Example 4 are reduced. Further analysis shows that the mechanical properties of the plastic bag prepared in Comparative Example 4 using silane coupling agent and chitosan instead of silane coupling agent modified chitosan are relatively low. It can be seen from the above that the silane coupling agent modified chitosan of the present invention can enhance the mechanical properties of the plastic bag.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.
Claims
1. A biodegradable plastic bag, characterized in that: The invention comprises the following ingredients: 60-80 parts of polylactic acid, 30-40 parts of PBAT, 10-17 parts of modified gluten powder, 5-10 parts of chitosan modified by silane coupling agent, 0.5-1 parts of lubricant, and 0.1-0.5 parts of antioxidant; The preparation process of the modified gluten is as follows: (1) adding gluten powder to water and uniformly dispersing it by ultrasonication to obtain solution A; (2) adding ε-polylysine and cucurbituril to water and uniformly dispersing them by ultrasonication to obtain solution B; (3) mixing the solution A and the solution B, adding glutaminase to perform enzymatic hydrolysis, and freeze-drying the reaction solution to obtain modified gluten powder; In step (2), the mass ratio of ε-polylysine to cucurbituril and water is 1:3-5:20-30, and the cucurbituril is cucurbituril [6]; The preparation process of the silane coupling agent modified chitosan is as follows: chitosan and silane coupling agent are mixed according to a mass ratio of 1:0.3-0.5, heated to 80-90°C for reaction for 2-3h, and silane coupling agent modified chitosan is obtained; the silane coupling agent is selected from one of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-570.
2. The biodegradable plastic bag according to claim 1, characterized in that: The mass ratio of gluten powder to water in step (1) is 1:1-2.
3. The biodegradable plastic bag according to claim 1, characterized in that: The temperature of the enzymatic hydrolysis reaction in step (3) is 40-45° C., the pH is 6-7, the time is 4-8 hours, the enzyme activity of the glutaminase is 1000 U / g, and the amount of glutaminase used is 0.5-1% of the mass of the gluten powder.
4. The biodegradable plastic bag according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 1076.
5. The biodegradable plastic bag according to claim 1, characterized in that: The lubricant is stearyl stearate or paraffin.
6. The method for preparing a biodegradable plastic bag according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: vacuum drying each component, heating the component to 180-200° C., keeping the temperature for 1-2 hours to obtain a mixture, and extruding the mixture and cooling the mixture to form the mixture.
7. The method for preparing a biodegradable plastic bag according to claim 6, characterized in that: The vacuum drying temperature is 90-100° C. and the time is 0.8-1 h.
Citation Information
Patent Citations
Easily degradable environment-friendly plastic bag
CN108676202A
Enzymatic gelatin-based hydrogel with controllable blood-coagulation and antibacterial properties and preparation method of hydrogel
CN111068102A
Antibacterial puncture-resistant biodegradable packaging bag and preparation method thereof
CN112940474A